Camidanlumab tesirine, an antibody-drug conjugate, in relapsed/refractory CD25-positive acute myeloid leukemia or acute lymphoblastic leukemia: A phase I study. (August 2020) - Goldberg, Aaron D.; Atallah, Ehab; Rizzieri, David; Walter, Roland B.; Chung, Ki-Young; Spira, Alexander; Stock, Wendy; Tallman, Martin S.; Cruz, Hans G.; Boni, Joseph; Havenith, Karin E.G.; Chao, Grace; et al.
Graphical abstract: The mechanism of action of camidanlumab tesirine . Camidanlumab tesirine binds to the CD25 antigen on AML/ALL tumor cells. Upon binding, the ADC is internalized and releases PBD dimers after the protease-sensitive linker is cleaved in lysosomes. The released PBD molecules migrate into the nucleus and sequence-selectively bind to the DNA minor groove, forming inter-strand cross-links that block tumor cell division and, hence, directly kill the cell. ADC, antibody-drug conjugate; ALL, acute lymphoblastic leukemia; AML, acute myeloid leukemia; PBD, pyrrolobenzodiazepine. Highlights: Camidanlumab tesirine demonstrated an acceptable safety and tolerability profile in adults with R/R CD25+ ALL or AML. The maximum tolerated dose was not reached at the investigated doses, with only one dose-limiting toxicity observed. Camidanlumab tesirine demonstrated modest efficacy, with two complete remissions in patients with R/R CD25+ AML with a weekly dosing schedule These results warrant possible further investigation of camidanlumab tesirine and/or combination treatments in patients with R/R CD25+ acute leukemia. Abstract: There is a significant need for improved therapeutics in older patients with acute leukemia. Camidanlumab tesirine is an antibody-drug conjugate against CD25, an antigen expressed in several malignancies, including acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). This open-label, dose-escalation and -expansion study (NCT02588092 ) assessed the safety, activity, pharmacokinetics (PK), and immunogenicity of camidanlumab tesirine in patients with relapsed/refractory ALL/AML. A total of 35 patients (34 AML and 1 ALL) were enrolled and received camidanlumab tesirine intravenously at 3–92 μg/kg once every three weeks (Q3W, n = 26) or 30 or 37.5 μg/kg every week (QW, n = 9). One dose-limiting toxicity of maculopapular rash occurred in the 30 μg/kg QW group; the maximum tolerated dose was not reached. No additional safety concerns or adverse events (AEs) of interest were identified. The most common (>10 % of patients) Grade ≥3 treatment-emergent AEs were febrile neutropenia (25.7 %), lymphopenia, neutropenia, thrombocytopenia or fatigue (all 14.3 %), pneumonia, increased gamma-glutamyltransferase, and hypophosphatemia (each 11.4 %). No signal for serious immune-related AEs such as Guillain-Barré syndrome/polyradiculopathy was observed and there was no evidence of immunogenicity. PK showed rapid clearance with apparent half-life <2 days for conjugated and total antibody, suggesting that Q3W dosing may be insufficient for therapeutic efficacy, and prompting exploration of a QW schedule. Two patients achieved complete responses with incomplete hematologic recovery; one each at 30 and 37.5 μg/kg QW. The trial was terminated during dose escalation due to programmatic reasons other than safety. Hence, recommended dose was not determined.